The Relationship between Teacher Pedagogic Competence and Playgroup Class Management Ability in Oebobo District - Maria Rosalia Ego; Sartika Kale; Angelikus Nama Koten (Early Childhood Education Development and Studies (ECEDS), 2021)
The purpose of this research is to find out the relationship between the pedagogical competencies of teachers and the ability to manage classes in play groups in Oebobo Subdistrict. This study used a quantitative approach with a population of 84 teachers in a playing group in Oebobo Subdistrict which was divided based on the last level of education and sample withdrawal was carried out using disproportionate stratified random sampling with a sample of 42 teachers. Data taken using questionnaires and statistic techniques used to test hypotheses are correlation pearson product moment. The results showed that there is a very strong and positive relationship between pedagogic competence and class management ability in the playing group in Oebobo Subdistrict.